Emerging Role for MAIT Cells in Control of Antimicrobial Resistance. Issue 6 (June 2021) - Leeansyah, Edwin; Boulouis, Caroline; Kwa, Andrea Lay Hoon; Sandberg, Johan K.
Abstract : Antimicrobial resistance is a serious threat to global public health as antibiotics are losing effectiveness due to rapid development of resistance. The human immune system facilitates control and clearance of resistant bacterial populations during the course of antimicrobial therapy. Here we review current knowledge of mucosa-associated invariant T (MAIT) cells, an arm of the immune system on the border between innate and adaptive, and their critical place in human antibacterial immunity. We propose that MAIT cells play important roles against antimicrobial-resistant infections through their capacity to directly clear multidrug-resistant bacteria and overcome mechanisms of antimicrobial resistance. Finally, we discuss outstanding questions pertinent to the possible advancement of host-directed therapy as an alternative intervention strategy for antimicrobial-resistant bacterial infections. Highlights: Host immunity is an important factor in clearing antibiotic-resistant bacterial infections that is often neglected. Understanding host immunity can provide novel insights for alternative intervention strategies against antimicrobial resistance. Mucosa-associated invariant T (MAIT) cells are key players in human antibacterial immunity. These highly abundant unconventional T cells recognise by-products from bacterial vitamin B2 biosynthesis, and mediate bacterial control through direct killing and orchestrating downstream immune responses. MAIT cells have the capacity to control drug-resistant bacteria and overcome resistance. This suggests that MAIT cells may participate in the clearance of bacteria that acquire resistance during antibiotic therapy and may provide protection against infections by resistant bacteria. Enhancing MAIT cell properties may be a viable prophylaxis and alternative treatment strategy in vulnerable populations.